The stability of electron-positron jets in laboratory plasmas - Arrowsmith, CD (2024)
Relativistic electron-positron plasmas are found in extreme astrophysical environments such as black hole and neutron star magnetospheres, where accretion-powered jets and pulsar winds are expected to be enriched with electron-positron pairs. Their role in the dynamics of these environments is in many cases believed to be fundamental, but their collective plasma behaviour is expected to differ significantly from typical electron-ion plasmas due to the matter-antimatter symmetry of the charged components. Therefore, many attempts have been made over previous decades to generate electron-positron plasmas and study them in the laboratory. But so far, the challenge of producing large enough yields of positrons in quasi-neutral beams has restricted understanding to simple numerical and analytical studies. In this thesis, a novel scheme for generating high-density, quasi-neutral, relativistic electron-positron pair beams has been developed, using an ultra-relativistic proton beam at CERN’s Super Proton Synchrotron (SPS). The achieved increase in electron-positron yield is orders of magnitude greater than neutral pair beams reported at high-power laser facilities, representing a key milestone, as the beams exceed characteristic scales necessary for collective plasma behaviour. This opens up the possibility of directly probing the microphysics of pair plasmas beyond quasi-linear evolution into regimes that are challenging to simulate or measure via astronomical observations. In the first application of this new experimental platform, pair beam-plasma instabilities are investigated by propagating the pair beam through a metre-length plasma. Due to their fast growth rates, pair beam-plasma instabilities are invoked to explain observations of γ-ray bursts and active galactic nuclei (AGN) jets, but theories expect the growth rates to be drastically reduced when non-idealized conditions are considered. The assertion that such instabilities can explain the lack of observed cascade γ-ray emission from TeV-blazars has been challenged using simplistic theoretical arguments, but in this work, theories are tested in the laboratory for the first time.